Analisis Penyebab Keterlambatan Bongkar Muat Barang Akibat Faktor Peralatan (Studi Kasus : Dermaga A Pelabuhan Dumai) - Muhammad Safrianda; Rinaldi Rinaldi; Ferry Fatnanta (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Port is defined as the intersection of land and water transportation nodes withloading and unloading activities of goods. The loading and unloading activities requiredecent equipments to support process. Any equipment that fails to function properly willgreatly delay the loading and unloading process in the port.Several factors that affect loading and unloading delay of goods are due to disabledequipment and human error which are classified into technical factors. These technicalfactors include broken equipment and human errors such as pending truck and operatorarrival.Based on the analysis on PT. Antarindo Wahana Cargo, the company that performsthe loading and unloading activities in Dumai Port A, the main factor which contributes tothe delay was broken equipments. The worst idle time that occurs due to the brokenequipments was 0,69% (5 hours) during February 2015. The offered solution to minimizethe idle time due to the broken equipments: 1) periodic maintenance especially for oldequipments, and 2) renting other equipment to replace the broken equipment so theloading and unloading process could be done timely.Keywords : port, idle time, loading and unloading, equipment, broken equipment